LPWAN Occupancy Model Parameter Identification for License Exempt sub-GHz Frequency Bands - Rauh, Sebastian; Robert, Jörg; Schadhauser, Michael; Heuberger, Albert (German Microwave Conference (GeMiC), 2018)
For many applications Low Power Wide Area Net- works (LPWANs) are an appealing method to provide cost- efficient connectivity to many small and battery-driven devices spread over large areas. However, LPWANs are typically oper- ated in the license exempt sub-GHz frequency bands. This means they have to share the spectrum with other devices also operated in these bands, which can impair the LPWAN signals. In order to analyze the impact of interference on LPWAN signals the IEEE 802.15 Interest Group LPWA has defined an interference model that can be used for detailed Physical Layer (PHY) simulations. In order to define suitable parameter sets for this interference model we propose a processing framework based on image processing. This framework allows a broadband analysis of license exempt frequency bands. It is able to identify signal parameters such as access length, arrival rate, center frequency, and bandwidth. These obtained values can then be used as input parameters of the IEEE 802.15 interference model or other channel occupancy models. We present exemplary measurement results that we obtained during a field trial as part of the so- called Betriebs-Adaptive Tracking Sensorsysteme (BATS) project in Berlin, Germany and show the derived parameter sets.
Keywords: Occupancy Model; Interference Model; LPWAN; Image Processing